A produção da neodocência no ensino médio na segunda metade do século XX: entre a eficência pedagógica e a renovação curricular - Sfredo, Marta Luiza (Universidade do Vale do Rio dos Sinos, 2019)
The aim of the research is to analyze how teaching for Brazilian high school was being produced from the printed pedagogic published in Brazil in the second half of the twentieth century, considering the relation between state, economy and education. Such relations are marked by the emergence of precariousness, as an expression of a neoliberal economic development project, which involves the configurations of a “neobloke”, manufactured under the aegis of competitiveness, utilitarianism and individualization. The methodology proposed for this study involved document analysis, oriented by the concept of “social epistemology” proposed by Thomas Popkewitz contrasted with the theorizations by Laval and Dardot (2016). The results of the analysis pointed to the production of a “neo-teaching” for high school, based on the principle of pedagogical efficiency and curricular renewal, in terms of the excellence, based on permanent innovation and the ability of adaptation in the face of constant changes. This is manifested in the design of a “Copernican revolution” for education, positioning the student as the center of the educational process and relegating the teacher to a learning facilitator. Another dimension found was the emphasis on the construction of a new curriculum capable of orienting the pedagogical work towards “learning for life”, an expression of the development of an increasingly practical teaching. Indicatives that denote that the rationalities of neoliberal policies began to operate at the core of the teacher's activity, influencing the didactic orientations, conceived as a set of entertainment techniques that bring teaching to a pinball; of planning as a teaching strategy linked to the development of educational dynamics translated into instructional technology and the teaching objectives considered essential competences for class management. Under such conditions, the appreciation of the common as an educational principle emerges as an alternative to the economist contours that make up a “neo-teaching” for Brazilian high school.

El objetivo de la investigación es analizar cómo se ha producido la enseñanza para la escuela secundaria brasileña a partir de los impresos pedagógicos publicados en Brasil en la segunda mitad del siglo XX, considerando la relación entre el Estado, la economía y la educación. Dichas relaciones están marcadas por el surgimiento de la precariedad, como expresión de un proyecto de desarrollo económico neoliberal, que involucra las configuraciones de un "neosujeto", fabricado bajo los auspicios de la competitividad, utilitarismo y individualización. La metodología propuesta para este estudio incluyó el análisis de documentos, orientado por el concepto de "epistemología social" propuesto por Thomas Popkewitz en contraste con las teorizaciones de Laval y Dardot (2016). Los resultados del análisis apuntan para la producción de una "neo-enseñanza" para la escuela secundaria, basada en el principio de la eficiencia pedagógica y la renovación curricular, en términos de búsqueda por la excelencia en los resultados, basada en la innovación permanente y en la capacidad de adaptación ante los constantes cambios. Este proceso se manifiesta en el diseño de una "revolución copernicana" para la educación, posicionando el estudiante como centro del proceso educativo y relegando el maestro a un facilitador de aprendizaje. Otra dimensión encontrada fue el énfasis en la construcción de un nuevo plan de estudios capaz de orientar el trabajo pedagógico hacia el "aprendizaje para la vida", una expresión del desarrollo de una enseñanza cada vez más práctica. Indicadores que denotan que las racionalidades políticas neoliberales comenzaron a operar en el centro de la actividad docente, influyendo en las orientaciones didácticas, concebidas como un conjunto de técnicas de entretenimiento que acercan la enseñanza a un pinball; de la planificación como una estrategia de enseñanza vinculada al desarrollo de dinámicas educativas traducidas en tecnología educativa y de los objetivos de enseñanza considerados competencias esenciales para la gestión de la clase. Bajo tales condiciones, la valorización de lo comun como principio educativo surge como una alternativa a los contornos economistas que conforman una "neo-enseñanza" para la escuela secundaria brasileña.
Keywords: Ensino Médio; Docência; Impressos pedagógicos; Neoliberalismo; High School; Teaching; Printed Pedagogic; Neoliberalism; Escuela secundaria; Enseñanza; Impressos pedagógicos; Neoliberalismo; ACCNPQ::Ciências Humanas::Educação